(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
This study focused on showing impact of the investment climate in the Iraqi private sector and was province of Baghdad a model. Importance of the study came from importance of the local private sector and its role in the Iraqi economy, and the Iraqi private sector is affected significantly from the investment climate, since the latter in which leads and directs the Iraqi private sector. This study is generated during the fundamental problem, which is weakness of the local private sector and its inability to compete with imported goods, which led to a decline the production system flexible in Iraq, which was caused by the investment climate. The study concluded to number of the conclusions, the most important that the investment climate in Iraq worsening significantly, and that the province of Baghdad is the more conservative deterioration of the investment climate after 2003, and that the investment climate a significant impact on the domestic investor in the province of Baghdad. And most important, as recommended by the study unite between the political blocs and make a goal and one that enhances the security and political stability, it would reduce the internal conflicts, as it prevents the entry of terrorism, which positively affect the security, and the author of the policy that makes stability investment climate of the first goals of the reform of the investment climate, and begin to gradually reform the investment climate of factors, the most serious to least serious, any of the absence of security to corruption ... etc.